(3GdcQGOI GdTQbjI (B:s (3OQGSI LZQGajI(B-(3JGQjNjI(B-(3JQGKjI (B/s - (3GdSYOj, YHGS aGVd,s 1941- ((3HZOGO (B:s (3hRGQI GdKbGaI, eTQhY HZOGO YGUeI GdKbGaI GdYQHjI,s, 2013)
(3jMcj GdcJGH Yf GdcQGOI GdTQbjI GdbSe GdLfhHj ef TQbj HZOGO, MjK OQSJ LhGfHgG GdJGQjNjI hGdLZQGajI hGdJQGKjI(B. (3GTJb GSegG ef GdcQhO, hgj hSGFd Qj jJe HhSGWJgG QaY GdejGg ef GdfgQ Edi GdeRGQY, hJe OQGSI eMdGJgG hLZQGajJgG GdWHjYjI hJGQjNgG efP GdYgO GdcdOGfj Edi GdhbJ GdMGVQ, ceG OQSJ NUGFUgG GdScGfjI, hGSJKeGQ CQGVjgG hCfeGW fTGWgG GdGbJUGOj, aVdG Yf OQGSI JQGKgG GdTYHj heRGQ GdSjO EOQjS ajgG(B.s
(3GdZdGa (B: (3fhQS fHjd ; GdWHGYI GdEdcJQhfjI hGdJUMjM hGdENQGL Gdafj (B: (3OGQ GdTDhf GdKbGajI(B.s
(3cTGaGJ (B: (3UaMI (B469-476.s
(3HHdjhLQGajI (B: (3UaMI (B425-468.s
Keywords: (3GdcQGOI (B((3GdYQGb(B)s -- (3JGQjN bOjes; (3GdcQGOI (B((3GdYQGb(B)s -- (3LZQGajGs